Humans as Agents in the Termination of the African Humid Period - Wright, David K. (Frontiers in Earth Science, 2017)
There is great uncertainty over the timing and magnitude of the termination of the African Humid Period (AHP). Spanning from the early to middle Holocene, the AHP was a period of enhanced moisture over most of northern and eastern Africa. However, beginning 8000 years ago the moisture balance shifted due to changing orbital precession and vegetation feedbacks. Some proxy records indicate a rapid transition from wet to dry conditions, while others indicate a more gradual changeover. Heretofore, humans have been viewed as passive agents in the termination of the AHP, responding to changing climatic conditions by adopting animal husbandry and spreading an agricultural lifestyle across the African continent. This paper explores scenarios whereby humans could be viewed as active agents in landscape denudation. During the period when agriculture was adopted in northern Africa, the regions where it was occurring were at the precipice of ecological regime shifts. Pastoralism, in particular, is argued to enhance devegetation and regime shifts in unbalanced ecosystems. Threshold crossing events were documented in the historical records of New Zealand and western North America due to the introduction of livestock. In looking at temporally correlated archaeological and paleoenvironmental records of northern Africa, similar landscape dynamics from the historical precedents are observed: reduction in net primary productivity, homogenization of the flora, transformation of the landscape into a shrub-dominated biozone and increasing xerophylic vegetation overall. Although human agents are not seen as the only forces inducing regime change during the termination of the AHP, their potential role in inducing large-scale landscape change must be properly contextualized against other global occurrences of neolithization.